Killing floor - Child, Lee (Child, Lee. Jack Reacher novel, 1997)
A discharged soldier is framed for a murder by the chief of police in a small town in Georgia where he has just arrived. When the soldier learns that the murdered man was his brother he breaks out of jail and carries out his own investigation.